DERIVATIONAL MORPHEMES IN THE BOOKSTORE SISTERS SHORT STORY BY ALICE HOFFMAN: A Morphological Analysis - Laila, Destia Nur; Noryatin, Yeni; Arvian, Elsan (Sekolah Tinggi Bahasa Asing JIA, 2025)
This study aims to analyze words to find out the types of derivational morphemes and morphological processes contained in the short story Bookstore Sisters by Alice Hoffman. This study applies the descriptive qualitative method, using the theoretical frameworks proposed by Katamba & Stonham (2006) and Kridalaksana (2010). From the result of this research, the words can be categorized based on the type of derivational morpheme: the first is suffixes with thepercentage of 80%. The second is prefixes, they have a percentage of 20%. The result of the morphological process can be categorized based on part of speech into eight types. In terms of morphological processes, derivational morphemes most commonly produce adverbs, followed by adjectives and nouns, with several processes occurring without changes in word class but resulting in semantic modification. These results indicate that derivational affixation plays a significant role in shaping word formation in literary texts. This study contributes to morphological studies by providing empirical evidence of derivational processes in English short stories and may serve as a reference for further linguistic and literary research.